2022
DOI: 10.1002/agj2.21035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environment on combining ability, heterosis for seed cotton yield in Bt introgressed lines of upland cotton

Abstract: Successful hybrid development work in cotton involves unearthing information of combining ability, heterosis and per se performance of the genetic material. This study involved multi‐environment estimation of combining ability and heterosis along with the stability of per se performance using Bt cotton genetic materials for seed cotton (Gossypium hirsutum L.) yield. Combining ability analysis across environments showed significant effects on the performance of genotypes, general combining ability (gca), specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The results showed that genotypes, parents, crosses, parents vs. crosses, lines, testers and line x tester recorded highly significant for all studied traits except for uniformity index of lines. Similar results were reported by Lingaraja et al (2017), Tigga et al, (2017), Al-Hibbiny et al, (2020, , Samak et al, (2022) and Farooq et al, (2023).…”
Section: Analysis Of Variancesupporting
confidence: 90%
“…The results showed that genotypes, parents, crosses, parents vs. crosses, lines, testers and line x tester recorded highly significant for all studied traits except for uniformity index of lines. Similar results were reported by Lingaraja et al (2017), Tigga et al, (2017), Al-Hibbiny et al, (2020, , Samak et al, (2022) and Farooq et al, (2023).…”
Section: Analysis Of Variancesupporting
confidence: 90%